Splenocolic fistula in a patient with diffuse large B-cell lymphoma: A case report and review of literature - Luca, Tonia; Sergi, Mauro; Coco, Onella; Leone, Emanuela; Chisari, Giulia; Fontana, Paolo; Castorina, Sergio (Frontiers in Surgery, 2022)
Fistula that connects the bowel to other organs, such as urinary bladder or small intestine, is a relatively frequent complication, often associated with inflammatory diseases such as diverticulitis, Crohn's disease, colorectal cancer or lymphoma. Splenocolic fistula is an extremely rare condition described in literature. It can occur in cases of splenic tumors, including splenic diffuse large B cell lymphoma. We report the case of an 82-year-old man who presented with melaena, worsening asthenia, hypotension, abdominal pain in the left flank and in the ipsilateral lumbar region. Ultrasound and computed tomography documented splenomegaly, thickening of the splenic flexure of the colon and the presence of a fistulous passage between colon and the splenic hilum. The diagnosis of lymphoma was made following laparotomy and caudal splenopancreatectomy. Due to the aggressive clinical behavior of this type of lymphoma, splenectomy is the main treatment in patients with splenomegaly, abdominal pain and tumor expansion